Comparison of ocular surface assessment outcomes between healthy controls and patients with obstructive sleep apnea–hypopnea syndrome: a meta-analysis of the literature - Jian Sun; Jie He; Zongan Liang (Frontiers in Physiology, 2023)
Objective: This meta-analysis aims to determine whether ocular surface alterations are associated with disease severity in patients with obstructive sleep apnea–hypopnea syndrome (OSAHS).Methods: The protocol for this systematic review and meta-analysis was registered in PROSPERO. We conducted the search in six electronic databases (China National Knowledge Infrastructure, EMBASE, Cochrane Library, Web of Science, Wanfang, and PubMed) from since the construction of the databases to 30 December 2022. The standard mean difference (SMD) and correlation coefficients are reported as measures of the effect size in the presence of retrieved data. In addition, the random effects model or fixed effects model was used in a combined analysis. Stata 11.0 and R 3.6.1 were used for statistical analyses of the data.Results: A total of 15 studies satisfied the inclusion criteria for this study. The prevalence of floppy eyelid syndrome (FES) and dry eye syndrome in patients with obstructive sleep apnea–hypopnea syndrome was 40 and 48%, respectively. In addition, the Schirmer 1 value and tear break-up time (TBUT) were remarkably reduced in patients with OSAHS when compared to that of the controls. The ocular surface disease index (OSDI) scores, Oxford corneal staining scores, and the rates of loss in the meibomian glands were elevated in patients with obstructive sleep apnea–hypopnea syndrome when compared to that of the controls, especially those with severe disease. Moreover, the Schirmer 1 value and tear break-up time exhibited a negative correlation with the apnea–hypopnea index (AHI), and the OSDI showed a positive association with the apnea–hypopnea index.Conclusion: Patients with OSAHS had a greater prevalence of FES than the healthy controls. They also showed lower Schirmer 1 value and tear break-up time but had a higher OSDI, Oxford corneal staining scores, and rates of loss in the meibomian glands than the healthy controls.Clinical Trial Registration: (https://www.crd.york.ac.uk/prospero/display_record.php?RecordID=392527).